Diagnostic Accuracy of First-Trimester Uterine Artery Pulsatility Index in Predicting Preeclampsia Among Primigravida - Zahra, Shan E; Kamal, Mahjabeen Mahmood; Awan, Muhammad Wasim; Zahra, Fatima Tuz; Ishtiaq, Bushra; Iqbal, Shaghaf (Biological and Clinical Sciences Research Journal, 2025)
Preeclampsia (PE) remains a major cause of maternal and perinatal morbidity and mortality worldwide. Early prediction using first-trimester uterine artery pulsatility index (UtA-PI) has been proposed to identify women at risk, but its diagnostic performance in low-risk primigravidae remains uncertain. Objective: To evaluate the diagnostic accuracy of first-trimester mean UtA-PI for predicting PE among primigravidae and to describe associated maternal and neonatal outcomes. Methods: We conducted a prospective diagnostic-accuracy study in primigravida women at 11+0–13+6 weeks. Bilateral UtA Doppler was performed and mean UtA-PI and MoM were recorded. Participants were followed to delivery; PE was ascertained using standard criteria. Group comparisons used Welch’s t-test for continuous variables and chi-square/Fisher’s exact tests for categorical variables. Diagnostic accuracy was assessed using a predefined threshold (UtA-PI MoM ≥2.5) and receiver operating characteristic (ROC) analysis. Results: Of 160 women, 8 (5.0%) developed PE. Baseline characteristics were similar between groups, except higher pre-scan diastolic BP in women who later developed PE (76.88 ± 4.22 vs 71.88 ± 8.23 mmHg; p = 0.0121). First-trimester mean UtA-PI and MoM were not significantly different between PE and non-PE groups (both p > 0.39). Peak SBP/DBP during pregnancy were higher in PE (141.38 ± 12.35 vs 121.68 ± 11.22 mmHg, p = 0.0025; 104.38 ± 6.25 vs 76.78 ± 8.87 mmHg, p < 0.0001). Using UtA-PI MoM ≥2.5, there were 0 true positives, 0 false positives, 8 false negatives, and 152 true negatives (sensitivity 0.0%, specificity 100.0%, NPV 95.0%, accuracy 95.0%). ROC analysis for mean UtA-PI MoM showed limited discrimination (AUC = 0.585). Conclusions: In this primigravida cohort, first-trimester mean UtA-PI demonstrated limited standalone predictive value for PE, while adverse maternal hemodynamics and neonatal outcomes were evident among PE cases. Screening strategies should consider gestational-age–specific centiles and integration with clinical/biochemical markers rather than UtA-PI alone.